2012
DOI: 10.1111/j.1365-2354.2012.01368.x
|View full text |Cite
|
Sign up to set email alerts
|

Diet components associated with perceived fatigue in breast cancer survivors

Abstract: Little is known about the contribution of diet components independent of body composition to persistent fatigue in breast cancer survivors. Therefore, our study aim was to determine the associations among dietary intake and fatigue in relation to and independent of adiposity and physical activity (PA) in breast cancer survivors. Baseline data from 42 breast cancer survivors enrolled in a randomized exercise trial were analyzed: fatigue (FACT-F), diet components (3-day diet record), body mass index, percent bod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
44
1
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 34 publications
(48 citation statements)
references
References 45 publications
(69 reference statements)
2
44
1
1
Order By: Relevance
“…Our findings are consistent with previous observational studies that found higher quality diets [27, 32], as well as diets high in fiber [30], fruits, and vegetables [1], omega-3 fatty acids relative to omega-6 fatty acids [2] were associated with a lower likelihood and less severe persistent fatigue in breast cancer survivors. In contrast to our study, which emphasized at least two servings per day of omega-3 fatty acid-rich foods, and thus encouraged targeted fat consumption, one study found that diets high in fat were associated with increased fatigue [30].…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…Our findings are consistent with previous observational studies that found higher quality diets [27, 32], as well as diets high in fiber [30], fruits, and vegetables [1], omega-3 fatty acids relative to omega-6 fatty acids [2] were associated with a lower likelihood and less severe persistent fatigue in breast cancer survivors. In contrast to our study, which emphasized at least two servings per day of omega-3 fatty acid-rich foods, and thus encouraged targeted fat consumption, one study found that diets high in fat were associated with increased fatigue [30].…”
Section: Discussionsupporting
confidence: 92%
“…This combing of types of fat could obscure the association between fatigue and various types of fat. This same study also did not find an association between fruit and vegetable consumption and fatigue [30]. Unlike our study, fruit and vegetable intake was combined, and mean intake was 2.7 servings per day, which is lower than the 3.5 servings per day in our participants at baseline.…”
Section: Discussioncontrasting
confidence: 84%
See 2 more Smart Citations
“…However, there is a paucity of information on the relationship between FM and fatigue in cancer populations. One study in women with breast cancer reported a significant, albeit weak, correlation between percentage body fat and fatigue ; however, another study reporting on this relationship in patients with breast cancer did not find a significant association . Although findings to date are mixed, these results do raise the possibility that addressing increases in FM may also be an important target for the management of cancer‐related fatigue.…”
Section: Introductionmentioning
confidence: 94%